Editorial: Heavy Metal Toxicity in Plants: Recent Insights on Physiological and Molecular Aspects - Gill, Rafaqat Ali; Kanwar, Mukesh Kumar; Rodrigues dos Reis, Andre; Ali, Basharat (Frontiers in Plant Science, 2022)
The topmost soil (i.e., surface O and A) is of great importance for plants as it contains the majority of the mineral elements required for normal plant growth and development (PG&D). However, the same soil also serves as a sink for hazardous pollutants including heavy metals (HMs) such as cadmium (Cd), lead (Pb), chromium (Cr), arsenic (As), and mercury (Hg) concentrated due to anthropogenic activities (industrialization and urbanization) that severely impact on PG&D. These toxic metal ions after entering into plant body disturbed cell wall, cell membrane, the activity of mitochondria (root) and cytoplasm (leaf) induced MDA and ROS content, and negatively impact the antioxidative machinery, fatty acids (i.e., linoleic acid and linolenic acid), and some other enzymes such as NADPH oxidase, etc. Further, HM toxicity caused the disturbance of water and nutrient supply from soil to upper parts of plants and deterioration in the activities of leaf pigment such as chlorophyll content and PS II impact on the sugar production and then transportation system from upper to lower parts of plants. These above drastic changes altogether caused the alterations in the various physiological and biochemical processes resulted in the reduction of the fresh biomass (root and shoot), overall PG&D, and finally decreased the grain quantity and quality. To tackle this, the researchers explored various perspectives while studying plants grown under HMs stressed environments. First, they explored plant response mechanisms as they activate its enzymatic (SOD, POD, CAT, APX, and GR) and non-enzymatic (GSH and ASA) antioxidant machinery. Secondly, plants modify their cell wall and root exudates. The third strategy is the utilization of plants (phytoremediation-hyperaccumulation) to absorb more content of HMs from the soil. Fourth, overexpression of metal responsive genes such as PCR2, AT6, CDT1, and WRKY creates the protective shield against metal toxicity. Lastly, exogenous applications of growth regulators such as GA, H2S, and GSH provide relief to plant species coping hazardous behavior of HMs. In a nutshell, an integrated strategy based on above all alternatives can strengthen the plant defense system and increase the seed yield of the crop plants growing in the toxic environment.